Integrating Psychological Factors in the Learning Process at Pondok Modern Darussalam Gontor: Application of a Humanistic Approach to Learning - Zunaidah, Zunaidah; Rosyidah, Umi; Maftuhah, Maftuhah (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2025)
This research aims to discuss the learning process at Pondok Modern Darussalam Gontor with a focus on the implementation of a humanistic approach to teaching and learning, particularly integrating psychological factors. The teaching and learning activities are considered crucial means in creating individuals who can behave according to noble human values (khairu ummah). Therefore, teachers play a significant role in determining learning theories that align with students' needs. The research method employed is qualitative with a literature review approach, utilizing primary and secondary data sources from various references. This study suggests that the role of a teacher's "ruh" or soul holds greater importance than the teachers themselves. In the learning process, it is essential to consistently integrate the values of Panca Jiwa (Five Spirits) and implement the steps of learning such as al-ta'aruf (introduction), al-muqaddimah (preparation), al-‘ardu (subject matter), al-rabtu (practice), at-tatbīq (application), and al-ikhtitām (conclusion) effectively.